Three new aflatoxigenic species of Aspergillus section Flavi isolated in Portugal - Soares, Célia (2014)
Three new aflatoxin-producing species isolated from two Portuguese commodities, almonds and maize, are described. A polyphasic approach based on phenotypic (morphology and extrolites) and molecular characterizations was used to identify these isolates as belonging to new species. From the study of the twenty two isolates obtained in maize and almonds, two were identified as Aspergillus flavus, six as A. minisclerotigenes and four as A. parasiticus. Examination of morphological characters combined with the analyses of aflatoxins and CPA production and molecular data revealed that ten of the Aspergillus section Flavi strains that were isolated do not match that of described species of the section. The multilocus analyses were performed using different primers for DNA regions. Molecular characterization showed that A. mottae, A. sergii and A. transmontanensis are well supported by phylogenetic analyses of the combined data. Aspergillus transmontanensis and A. sergii are phylogenetically related to A. parasiticus. Aspergillus mottae is phylogenetically ancestral to A. flavus and A. parasiticus. Therefore three new species are proposed Aspergillus mottae, Aspergillus sergii and Aspergillus transmontanensis.